Translation as a paradigm shift - Pisanski Peterlin, Agnes (ELOPE (Ljubljana), 2013)
In recent decades the increasing reliance on computer technology and the emergence of electronic publishing have precipitated changes in both the production and reception of academic writing. At the same time, the dominance of English as the medium of academic communication has been asserted in all fields of study. While many scholars write their own texts in English, it is not exceptional for others to have their papers translated into English. It is interesting, however, that translation of academic discourse has received relatively little research attention so far. In the study presented here, the question how translated academic texts differ from comparable original English academic texts is addressed. To explore this question, a 700,000-word corpus comprising 104 research articles (Slovene-English translations and comparable English originals) is analyzed in terms of references to the entire text itself. The results show considerable differences between the translated texts and the comparable English-language originals.
Keywords: akademski diskurz; korpusna analiza; metadiskurz; prevajanje; translation; znanstveno pisanje; znanstveno prevajanje